2007
DOI: 10.2214/ajr.07.2393
|View full text |Cite
|
Sign up to set email alerts
|

Blinded Comparison of Computer-Aided Detection with Human Second Reading in Screening Mammography

Abstract: A human second reader or the use of a CAD system can increase the cancer detection rate, but we found no statistical difference between the two because of the small sample size. A possible benefit from a human second reader is that CAD systems can only point to possible abnormalities, whereas a human must determine the significance of the finding. Having two humans review a study may increase detection rates due to interpreter--hence, perceptual--variability and not just increased detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 20 publications
3
43
0
1
Order By: Relevance
“…Many studies have validated CAD techniques in screening populations and found a sensitivity ranging from 73 [2] to 96% [3]. Moreover, the impact of a CAD system on the performance of mammogram observers was evaluated in several studies [2,[4][5][6][7][8][9][10][11][12][13][14], showing that there is insufficient evidence to claim that CAD improves cancer detection rates but that it does increase recall rates in screening programs for breast cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have validated CAD techniques in screening populations and found a sensitivity ranging from 73 [2] to 96% [3]. Moreover, the impact of a CAD system on the performance of mammogram observers was evaluated in several studies [2,[4][5][6][7][8][9][10][11][12][13][14], showing that there is insufficient evidence to claim that CAD improves cancer detection rates but that it does increase recall rates in screening programs for breast cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…To improve performance of the single radiologist, double reading provides an approach. Several researches demonstrated that independent double interpretation of screening mammograms appears to be a useful tool to ensure the quality of early detection of breast lesions [7][8][9]. Although the double reading method can improve the detection rate of breast cancer, it is not a cost-effective method due to the scarcity of experienced radiologists by compare with the increasing large number of mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…The CAD (Image Checker, version 8.0 R2 Technology) showed the potential to increase the cancer detection rate for both FFDM (full field digital mammography) and screen-film mammography in breast cancer screen performed with independent double reading. Georgian-Smith et al [11] compared the CAD with a blinded human second reader for detection of additional breast cancer not seen by a primary radiologist. The research aimed to compare the practice of a human second reader with a CAD reader for the reduction of the number of false-negative cases resulting from review by a primary radiologist.…”
Section: Introductionmentioning
confidence: 99%